A study on mechanical performance of 3D printed wood mimic materials - Abid Fariduddin Mohd Fauzi; Zaliha Wahid; Nabilah Afiqah Mohd Radzuan; Nurhasyimah Abd Aziz; Afifah Zakiyyah Juri; Abu Bakar Sulong (Penerbit Universiti Kebangsaan Malaysia, 2024)
Wood has played a crucial role in the field of architecture, prototyping, and engineering, owing to its aesthetic appeal and specific mechanical properties tailored for diverse applications. The application 3D printing has facilitated the replication of natural materials like wood, enhancing both their visual and mechanical attributes. This research aims to investigate the mechanical properties of 3D printed PolyWoodTM materials and compare them with those of real wood composites. The mechanical property assessments conducted on PolyWoodTM samples encompass tensile, flexural, and compression tests. The obtained results are analyzed and compared with data from literature readings on real wood composites. The average tensile strength of PolyWoodTM material is 20.31 MPa, the flexural strength is 31.36 MPa, and the compression strength reaches up to 21.70 MPa. In comparison with real wood composites, the PolyWoodTM sample exhibits inferior performance in most mechanical properties. Regarding tensile strength, the performance of the material is comparable to other composite but is almost 50% lower than the Pure PLA performance. However, in term of Young’s Modulus, a significant difference is observed across all references, indicating more flexibility and larger elastic deformation under a given load for PolyWoodTM material. The differences on flexural strength were not obvious, with one research study showing lower strength. Finally, the compressive performance of real wood composites and pure PLA demonstrates superior resistance and strength when contrasted with PolyWoodTM materials.